A-136 The Transfer of Cognitive Training to Real-World Functioning: Results of our First Six Pilot Subjects at Six-Month Follow-Up. (30th August 2021) - Blake, Jason A; Mitchell, Brandon; McKay, Staci; Uswatte, Gitendra; Taub, Edward
Abstract: Objective: Currently, the majority of cognitive training research measures treatment efficacy using in-laboratory measures, with minimal focus on real-world treatment changes. This case series demonstrates the feasibility of transferring cognitive improvements from the laboratory into the everyday life setting. Method: This case series includes 6 chronic post-stroke participants; mild to moderate cognitive impairment. The intervention combines cognitive training with behavioral techniques, known as the Transfer Package (TP). The TP involves components that target functionality on IADLs in the real-world. Performance on cognitively-based IADLs in the real world are measured pre-treatment, post, and 6-month follow-up. Measures of real-world ability are the: Canadian Occupational Performance Measure (COPM), Cognitive Task Activity Log (CTAL) and Inventory of Improved and New Abilities (INCA). In-laboratory measures included the D-KEFS and Timed IADL assessments. Results: The real-world outcome measures used in this study were the COPM and two measures developed for this study, the CTAL and INCA. The mean change from pre to post on the COPM Performance Scale was 2.18 (SD = 1.33) and the mean change on the COPM Satisfaction Scale was 2.70 (SD = 1.27). The mean change on the CTAL was 1.96 (SD = 0.93). On the INCA, the mean number of improved real-world cognitive activities was 11.8 (SD = 4.9) and the mean number of new cognitive activities was 7.6 (SD = 3.9). Follow-up reported near-perfect retention on CTAL and continued improvement on the INCA. There were minimal changes on in-laboratory measures. Conclusions: This case series provides a framework for achieving the transfer of cognitive training treatment effects in the real-world life situation by overcoming behavioral barriers to functioning.